Hyperfiltration of ribes nigrum juice - Kertész Szabolcs (Review of faculty of engineering : analecta technica Szegedinensia, 2008)
Blackcurrant juicc is very popular among consumers due to its high content of mineral salts, C-vitamin. P-. BI-, B2- vitamin and provitamin A also. The scope of this study was to examine the applicability of a pilot scale reverse osmosis system for the concentration of different enzyme pretreated blackcurrant juice by AFC - 80 polyamide tubular membrane. With two pectinase enzyme preparation (Panzym Super E and Trenolin Rot DF) of the fresh juice for enzymatic depectinization was investigated. For description of the concentration process and the osmotic pressure model has been used. Van't Hoff model can be applied for the calculation of osmotic pressure differences dependence on the difference of concentrate and permeate concentration. Rautenbach model can be also used, which detennines the osmotic pressure in the knowledge of the concentration.